2007
DOI: 10.1007/s00203-007-0302-1
|View full text |Cite
|
Sign up to set email alerts
|

High level of soluble expression in Escherichia coli and characterisation of the CyaA pore-forming fragment from a Bordetella pertussis Thai clinical isolate

Abstract: Bordetella pertussis adenylate cyclase toxin-haemolysin (CyaA) can permeabilise erythrocytes by forming lytic pores. Here, a gene segment encoding CyaA pore-forming (CyaA-PF) domain cloned from genomic DNA of B. pertussis Thai isolate was over-expressed in Escherichia coli as a 126-kDa soluble protein which cross-reacted with anti-RTX monoclonal antibody. By co-expressing with acyltransferase CyaC, the CyaA-PF protein was found palmitoylated at Lys(983). Unlike E. coli lysate with the non-acylated form, the ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…An equal amount of erythrocytes lysed with 0.1% Triton X-100 was defined as 100% hemolysis. All samples were tested in triplicate for three independent experiments as previously described [21]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An equal amount of erythrocytes lysed with 0.1% Triton X-100 was defined as 100% hemolysis. All samples were tested in triplicate for three independent experiments as previously described [21]. …”
Section: Methodsmentioning
confidence: 99%
“…However, we have recently demonstrated that such palmitoylation at Lys 983 is not required for the binding of CyaA-Hly to target erythrocyte membranes, but rather needed for stabilizing CyaA-Hly-induced pores/channels [18]. Several studies clearly shown that, without the AC part, the CyaA-Hly domain can independently exert hemolytic activity against sheep erythrocytes that lack the CD11b/CD18 receptor, suggesting an alternative mechanism of target cell recognition via the RTX subdomain [19,20,21,22]. Nevertheless, the exact molecular mechanism of translocation of the AC domain across target cell membranes still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli BL21(DE3)pLysS harboring the recombinant plasmids pCyaAC‐PF encoding CyaA‐PF with CyaC, pCyaA‐PF (without CyaC) or pCyaC (Powthongchin & Angsuthanasombat, 2008), was grown at 30 °C in Luria–Bertani medium containing 100 μg mL −1 ampicillin. Protein expression was induced with 0.1 mM isopropyl‐β‐ d ‐thiogalactopyranoside (IPTG) for 5 h. Cultured cells were harvested by centrifugation at 5000 g (4 °C, 15 min), resuspended in 25 mM HEPES (pH 7.0) and disrupted via French Pressure Cell at 10 000 psi.…”
Section: Methodsmentioning
confidence: 99%
“…The pCyaC plasmid encoding the 21‐kDa CyaC‐acyltransferase (Powthongchin & Angsuthanasombat, 2008) was used as a template for single‐alanine substitutions at Ser 30 , His 33 and Tyr 66 , using a pair of mutagenic oligonucleotides as follows: S30A (f‐primer, 5′‐GATGAAC G CTCCCATGCA T CGCGACTGGCCGGT‐3′ and r‐primer, 5′‐GTCGCG A TGCATGGGAG C GTTCATCCACAGCCAG‐3′, with bold letters indicating changed nucleotides and underlined bases indicating a added NruI restriction site); H33A (f‐primer, 5′‐CCCATG GC CCGCGACTGG‐3′ and r‐primer, 5′‐CGCGG GC CATGGGAGAGT‐3′, with bold letters indicating changed nucleotides and underlined bases indicating an added NcoI restriction site); Y66A (f‐primer, 5′‐GTTGCA GCA TGCAGCTGGGC‐3′ and r‐primer, 5′‐GCTGCA TGC TGCAACCGGCA‐3′, with bold letters indicating changed nucleotides and underlined bases indicating a deleted PstI restriction site). All mutant plasmids were generated by PCR‐based directed mutagenesis using a high‐fidelity Pfu DNA polymerase, following the procedure of the QuickChange ™ Mutagenesis Kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation